1974
DOI: 10.1002/anie.197403761
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Hydroxamic Acids and N‐Hydroxyimides

Abstract: This progress report is concerned primarily with problems relating to the structure and reactions of hydroxamic acids and N-hydroxyimides, and also surveys some of the biological activities of these compounds. Particular significance attaches to the Lossen rearrangement of 0-acylated hydroxamic acids, which leads to isocyanates or their reaction products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
164
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 306 publications
(170 citation statements)
references
References 122 publications
(6 reference statements)
6
164
0
Order By: Relevance
“…Most of the previously reported Lossen rearrangement reactions take place only under alkaline conditions and/or through heating to a requisite temperature (20)(21)(22)(23). In the present study, we found that the reaction between BHA and TCBQ could occur at room temperature and under neutral or even weakly acidic pH.…”
Section: Major Reaction Product Of Bha Was Identified As O-phenylcarbsupporting
confidence: 59%
See 4 more Smart Citations
“…Most of the previously reported Lossen rearrangement reactions take place only under alkaline conditions and/or through heating to a requisite temperature (20)(21)(22)(23). In the present study, we found that the reaction between BHA and TCBQ could occur at room temperature and under neutral or even weakly acidic pH.…”
Section: Major Reaction Product Of Bha Was Identified As O-phenylcarbsupporting
confidence: 59%
“…It has been shown (20,21) that I could be formed through nucleophilic addition of phenyl isocyanate with a molecule of BHA: and II could be formed through the hydrolysis of phenyl isocyanate to aniline, followed by reaction of aniline with another molecule of phenyl isocyanate: The above analysis strongly suggests that phenyl isocyanate (Ar─N═C═O) should be formed as an initial unstable product during the reaction of BHA and TCBQ.…”
Section: Major Reaction Product Of Bha Was Identified As O-phenylcarbmentioning
confidence: 92%
See 3 more Smart Citations